2018
DOI: 10.1007/s12192-017-0855-0
|View full text |Cite
|
Sign up to set email alerts
|

Testicular torsion and reperfusion: evidences for biochemical and molecular alterations

Abstract: This study was done in order to determine the molecular and biochemical alterations following testicular torsion (TT) and torsion-reperfusion (TR). For this purpose, 54 male Wistar rats were divided into five groups as control group (n = 6) and experimental group subjected to 1, 2, 4, and 8 h unilateral left torsion induction (n = 12 in each group). After induction of TT, testicular samples were collected from each group (n = 6), and the other six rats of each group underwent the same period of reperfusion aft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
33
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(33 citation statements)
references
References 34 publications
0
33
0
Order By: Relevance
“…Very early studies have been shown that the torsion-induced loss of spermatogenesis is not due to Leydig and Sertoli cells to produce specific hormones, while it is partially related to germ cells apoptosis independent to Sertoli and/ or Leydig cells (Turner & Miller, 1997), which finally ends with arrested spermatogenesis and infertility (Turner, 1985). Lastly, we showed that the torsion at earlier stages (before 4 hr) results in apoptosis, while at developed stages (after 8 hr) it results in local necrosis (Shamsi-Gamchi, Razi, & Behfar, 2017).…”
Section: Introductionmentioning
confidence: 51%
See 2 more Smart Citations
“…Very early studies have been shown that the torsion-induced loss of spermatogenesis is not due to Leydig and Sertoli cells to produce specific hormones, while it is partially related to germ cells apoptosis independent to Sertoli and/ or Leydig cells (Turner & Miller, 1997), which finally ends with arrested spermatogenesis and infertility (Turner, 1985). Lastly, we showed that the torsion at earlier stages (before 4 hr) results in apoptosis, while at developed stages (after 8 hr) it results in local necrosis (Shamsi-Gamchi, Razi, & Behfar, 2017).…”
Section: Introductionmentioning
confidence: 51%
“…Testicular torsion results in infertility, and it has been reported that reperfusion, as an emergency therapeutic intervention, is necessary to ameliorate the torsion-induced pathogenesis against spermatogenesis (Wei, Huang, & Zhou, 2017;Yurtcu, Abasiyanik, Avunduk, & Muhtaroglu, 2008). It has been illustrated that the minimum of 1 hr results in testicular damage following testicular torsion in rats (Shamsi-Gamchi et al, 2017;Turner & Brown, 1993). Here in the present study, we tried to show the time-dependent effect of reperfusion after 4 hr torsion induction.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…Experimental studies of testis torsion by Shamsi-Gamchi et al reported a fall in total antioxidant capacity and GSH-Px levels with ischaemia-reperfusion injury, with an increase in MDA content. Again, the same study reported a great reduction occurred in spermiogenesis indexes and damage to the cell genome (Shamsi-Gamchi et al, 2018). and vitamin E were revealed to very effectively protect tissues from ischaemia-reperfusion injury in studies (Erdemir et al, 2017).…”
Section: Discussionmentioning
confidence: 85%
“…Molecular mechanisms have shown that reperfusion after surgical detorsion has a negative impact on the testicular parenchyma. 3 Current management continues to be surgical intervention with a subjective assessment of parenchymal reperfusion to decide whether or not the testicle is salvageable. 4 Intraparenchymal monitoring of testicular pressures has also shown how complex the reperfusion process can be after detorsion and the development of a compartment syndrome.…”
Section: Introductionmentioning
confidence: 99%